2022
DOI: 10.1093/oso/9780192865458.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Law and Policy in India

Abstract: This book studies environmental law and policy in India, which affects all sections of society. Those most deeply affected by it are the poor. They are the first victims of poor sanitation, polluted air, and contaminated water. Since the 1970s, efforts to protect environmental quality have met with limited success, posing enduring challenges for policy designers and decision-makers entrusted with protecting and preserving natural resources. This third edition retains the familiar analytical structure of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Where any offence under this Act has been committed by a company, every person who, at the time the offence was committed, was directly in charge of, and was responsible to, the company for the conduct of the business of the company, as well as the company, shall be deemed to be guilty of the offence and shall be liable to be proceeded against and punished accordingly: Provided that nothing contained in this sub-section shall render any such person liable to any punishment provided in this Act, if he proves that the offence was committed without his knowledge or that he exercised all due diligence to prevent the commission of such offence [33] . Notwithstanding anything contained in sub-section (1), where an offence under this Act has been committed by a company and it is proved that the offence has been committed with the consent or connivance of, or is attributable to any neglect on the part of, any director, manager, secretary or other officer of the company, such director, manager, secretary or other officer shall also ~ 78 ~ deemed to be guilty of that offence and shall be liable to be proceeded against and punished accordingly [34] . Explanation.…”
Section: Offences By Companiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Where any offence under this Act has been committed by a company, every person who, at the time the offence was committed, was directly in charge of, and was responsible to, the company for the conduct of the business of the company, as well as the company, shall be deemed to be guilty of the offence and shall be liable to be proceeded against and punished accordingly: Provided that nothing contained in this sub-section shall render any such person liable to any punishment provided in this Act, if he proves that the offence was committed without his knowledge or that he exercised all due diligence to prevent the commission of such offence [33] . Notwithstanding anything contained in sub-section (1), where an offence under this Act has been committed by a company and it is proved that the offence has been committed with the consent or connivance of, or is attributable to any neglect on the part of, any director, manager, secretary or other officer of the company, such director, manager, secretary or other officer shall also ~ 78 ~ deemed to be guilty of that offence and shall be liable to be proceeded against and punished accordingly [34] . Explanation.…”
Section: Offences By Companiesmentioning
confidence: 99%
“…In recent years, scientists have been carefully examining the various ways by which people affect the 'Environment'. They have found that we are causing air pollution, deforestation, acid rain, and other problems that are dangerous both to the earth and to ourselves [1] . Two international conferences on Environment and development -one at Stockholm in 1972 and another at Rio de Janerio in 1992 -have influenced environmental policies in most countries, including India.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Sharma (2002) specifically quotes a Hindu woman renouncer (sadhvi) who positioned the Tehri Dam issue in terms of the Hindu-Muslim struggle. Such understanding of the relations between Hindu nationalism and ecology is now permeated in the literature on the 2017 RoN case, failing to acknowledge India's much earlier development of its own activist constitutionally inspired regime of environmental jurisprudence (Divan & Rosencranz, 2002), more recently discussed by Gill (2017) and Amirante & Bagni (2022). Visvanathan (2017) regrets, referring to Stone (1972), that the Uttarakhand judgment could not be a 'full ecological agreement elaborating the idea of nature as having rights and possessing a standing', since 'the emphasis is more on the sacredness and historicity of Ganga and Yamuna'.…”
Section: Going Beyond Saffronisationmentioning
confidence: 99%
“…The Delhi High Court in a case 3 pronounced that: "…noise can well be regarded as a pollutant because it contaminates the environment, causes nuisance and affects the health of a person and would, therefore, offend the right to life, of Article 21, if it exceeds reasonable limits. it was also observed by the Court that the effect of noise on health has not yet full attention of our judiciary" 4 According to 'The Noise Pollution (Regulation & Control) Rules, 2000', the ambient air quality standards in respect of noise were described in a Schedule (See Rule 3(1) and 4(1)) 5 . The four zones are namely a) Industrial area: These are designated industrial area in any city where a bunch of industries will be established for manufacturing different products.…”
Section: Right To Religion and Noise Pollutionmentioning
confidence: 99%